Clinical Case A clinical case of severe hemorrhagic vasculitis - Lyudmila A. Filimonova; Julia A. Zgura; Roman A. Yaskevich; Evgeny L. Davydov; Maria L. Rossovskaya; Elena A. Delver; Ekaterina V. Kapustina (LLC "MEDIAFORMAT", 2024)
Diagnosis of systemic vasculitis often causes difficulties in clinical practice. A clinical case characterized by multiple organ and comorbid pathology is presented. The manifestation of intestinal bleeding was the reason for the diagnosis of severe ulcerative colitis. The appearance of a characteristic hemorrhagic rash, followed by renal pathology with hematuria and severe nephrotic syndrome, made it possible to establish the correct diagnosis.